Effects of Tonic Spinal Cord Stimulation on External Mechanical and Thermal Stimuli Perception Using Quantitative Sensory Testing: A Multicenter Stimulation ON-OFF Study on Chronic Pain Patients. Issue 3 (March 2020) - Bordeleau, Martine; Carrondo Cottin, Sylvine; Cantin, Léo; Gaudin, Daniel; Alnemari, Ahmed; Canuel, Jean-François; Fugère, François; Fournier-Gosselin, Marie-Pierre; Vollert, Jan; Prud'Homme, Michel
Abstract : Objectives: Tonic spinal cord stimulation (SCS) is currently used to treat neuropathic pain. With this type of stimulation, an implantable pulse generator generates electrical paresthesias in the affected area through 1 or more epidural leads. The goal of this study was to evaluate the impact of tonic SCS on the sensory perception of chronic pain patients using quantitative sensory testing (QST). Materials and Methods: Forty-eight patients (mean age: 57 y) with chronic leg pain due to failed back surgery syndrome or complex regional pain syndrome treated with SCS were recruited from 3 research centers. Test procedures included 2 sessions (stimulation On or Off), with measures of detection thresholds for heat, touch, vibration, and of pain thresholds for cold, heat, pressure, the assessment of dynamic mechanical allodynia, and temporal pain summation. Three different areas were examined: the most painful area of the most painful limb covered with SCS-induced paresthesias (target area), the contralateral limb, and the ipsilateral upper limb. Wilcoxon signed-rank tests were used to compare the mean difference between On and Off for each QST parameter at each area tested. P -values <0.05 were considered significant. Results: Regarding the mean difference between On and Off, patients felt less touch sensation at the ipsilateral area (−0.4±0.9 g, P =0.0125) and were less sensitive at the contralateral area for temporal pain summation (−4.9±18.1 on Visual Analog Scale 0 to 100, P =0.0056) with SCS. Discussion: It is not clear that the slight changes observed were clinically significant and induced any changes in patients' daily life. Globally, our results suggest that SCS does not have a significant effect on sensory perception. Abstract : Supplemental Digital Content is available in the text.